2014
DOI: 10.1007/s10461-014-0870-4
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to HIV and TB Care and Treatment, the Role of Food Security and Nutrition

Abstract: Food security and nutrition play an important role in HIV and TB care and treatment, including for improving treatment outcomes, adherence and uptake of HIV and TB care. This AIDS and behaviour supplement on ''Adherence to HIV and TB care and treatment, the role of food security and nutrition'' provides an overview of the current evidence and knowledge about the barriers to uptake and retention in HIV and TB treatment and care and on whether and how food and nutrition assistance can help overcome these barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…The African Food Security Network (AFSUN) 2008–2009 survey of patients with HIV/TB in 11 southern African cities showed that only 10% of patients with TB resided in food-secure households [ 35 ]. Food insecurity increases the risk of progression from latent to active disease, is a risk factor for infection, and can negatively impact on adherence [ 36 ]. A qualitative study in Swaziland found that some food-insecure patients stopped TB treatment because it increased their appetites when they were already food scarce [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The African Food Security Network (AFSUN) 2008–2009 survey of patients with HIV/TB in 11 southern African cities showed that only 10% of patients with TB resided in food-secure households [ 35 ]. Food insecurity increases the risk of progression from latent to active disease, is a risk factor for infection, and can negatively impact on adherence [ 36 ]. A qualitative study in Swaziland found that some food-insecure patients stopped TB treatment because it increased their appetites when they were already food scarce [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity has been associated with distress, depression, and anxiety (3335,5456). This may be a plausible explanation to the lack of adherence to treatment observed among food insecure HIV infected adults when compared to their food secure counterparts (32, 57). Previous evidence points in part, to psychological stress as a factor for reduced adherence to treatment among PLHIV (58, 59).…”
Section: Discussionmentioning
confidence: 99%
“…Employing a synergistic epidemic lens via the syndemics framework, food insecurity coexists and overlaps with the significant prevalence of HIV/AIDS in various regions in Africa. PWH experiencing food insecurity are likely to experience hunger, coupled with the side effects of ART, in the context of competing resources, which could increase the chances of treatment non-adherence [13]. In the context of food insecurity, evidence shows that HIV is a strong predictor of malnutrition, potentially increasing vulnerability to other comorbidities such as tuberculosis (TB) [14].…”
Section: Introductionmentioning
confidence: 99%